2014
DOI: 10.1007/s10147-014-0730-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic separation of gemcitabine and erlotinib in locally advanced or metastatic pancreatic cancer: therapeutic and biomarker results

Abstract: Purpose Erlotinib marginally improves survival when administered continuously with gemcitabine to patients with advanced pancreatic cancer; however, preclinical data suggest that there is antagonism between chemotherapy and Epidermal Growth Factor Receptor (EGFR) tyrosine kinase inhibitors when these are delivered concurrently. We tested a pharmacodynamic separation approach for erlotinib plus gemcitabine and interrogated EGFR signaling intermediates as potential surrogates for the efficacy of this strategy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…The detailed description of the selected studies is listed in Table 1 . Within the selected studies, there were five retrospective studies, 21 , 25 , 30 , 34 , 37 nine single-arm Phase II trials, 18 , 19 , 22 , 23 , 27 29 , 32 , 38 six Phase II RCTs, 26 , 31 , 33 , 35 , 36 , 39 three Phase III RCTs, 16 , 20 , 24 and one Phase Ib trial. 17 Among the studies, one RCT 16 and a retrospective study 34 investigated the difference between the GemErlo-treated arm and the gemcitabine monotherapy arm directly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed description of the selected studies is listed in Table 1 . Within the selected studies, there were five retrospective studies, 21 , 25 , 30 , 34 , 37 nine single-arm Phase II trials, 18 , 19 , 22 , 23 , 27 29 , 32 , 38 six Phase II RCTs, 26 , 31 , 33 , 35 , 36 , 39 three Phase III RCTs, 16 , 20 , 24 and one Phase Ib trial. 17 Among the studies, one RCT 16 and a retrospective study 34 investigated the difference between the GemErlo-treated arm and the gemcitabine monotherapy arm directly.…”
Section: Resultsmentioning
confidence: 99%
“…18 , 19 , 27 , 28 The first and second most common patterns of administration interval were “weekly for the first 3 weeks in a 4-week cycle” 23 , 27 30 , 33 , 35 , 36 , 39 and “weekly for the first 7 weeks in the first 8-week cycle then weekly for the first 3 weeks in a 4-week cycle”. 16 , 20 , 24 , 31 , 37 Erlotinib was administered at the dose of 100 mg/d in 17 studies, 19 , 20 , 23 , 25 – 36 , 38 , 39 100 or 150 mg/d in three studies, 16 , 17 , 21 and 150 mg/d in the remaining three studies. 18 , 22 , 24 …”
Section: Resultsmentioning
confidence: 99%
“…Several studies found that cfDNA and the presence of mutant KRAS in plasma or serum cfDNA was significantly associated with the metastasis in patients with cancer [ 28 , 33 , 38 , 48 ]. In recent years, many studies found that KRAS mutation was associated with the recurrence [ 49 – 51 ] and with survival prognosis in various types of cancer [ 32 , 35 ][ 38 ], but several studies suggested that KRAS mutation in cfDNA was not associated with survival outcome of patients with pancreatic, lung or colon cancer [ 14 , 25 , 33 ]. The prognostic values of KRAS mutations in cfDNA as a biomarker remain to confirm.…”
Section: Discussionmentioning
confidence: 99%
“…CA19-9 has traditionally been used as a surveillance tool, but has its limitations, namely low sensitivity and the fact that 5–10% of the population are incapable of producing CA19-9, rendering it useless in these patients [ 93 , 94 ]. ctDNA can be used for monitoring throughout treatments including surgery and chemotherapy [ 95 , 96 , 97 , 98 , 99 ].…”
Section: Current Clinical Utility Of Cfdnamentioning
confidence: 99%